Modification of self-assembled monolayers by electron irradiation: the effect of primary energy (10-500 eV) - Schmid, Martin; Zharnikov, Michael (The journal of physical chemistry. C, Energy, materials, and catalysis, 2019)
Well-defined alkanethiolate self-assembled monolayers (SAMs) represent a useful model system for a variety of thin organic films on solid supports, in particular in the context of their modification by electron irradiation. Taking a dodecanethiolate SAM on Au(111) as an example, we studied the primary electron energy dependence of the respective processes in the range of 10-500 eV. Cross sections of major irradiation-induced processes were derived, including thickness reduction, progressing chemical inhomogeneity, and damage of the SAM-ambient and SAM-substrate interfaces. All of the cross sections showed qualitatively similar behavior as functions of the primary electron energy, viz. a strong, progressive increase in the range of 10-100 eV and a nearly energy-independent character at the higher energies, up to 500 eV. This behavior was primarily attributed to the energy dependence of the ionization cross section, with a certain effect of the secondary electron yield. Quantitatively, the cross sections directly related to irradiation-induced bond breaking followed by desorption or relocation of the released fragments turned out to be noticeably higher (by a factor 2-2.5) than those representing the secondary processes in the SAM, such as reorganization of the SAM and SAM-ambient interface. The balance between the film decomposition, resulting in material loss, and cross-linking, resulting in the preservation of the material, was found to shift toward the decomposition at lower primary electron energies as compared to higher ones.
Gesehen am 08.01.2020